Use of laser capture microdissection to map hepatitis C virus-positive hepatocytes in human liver - Kandathil, Abraham J.; Graw, Frederik; Quinn, Jeffrey; Hwang, Hyon S.; Torbenson, Michael; Perelson, Alan S.; Ray, Stuart C.; Thomas, David L.; Ribeiro, Ruy M.; Balagopal, Ashwin (Gastroenterology, 2013)
Background & Aims Hepatitis C virus (HCV) predominantly infects hepatocytes, but many hepatocytes are not infected; studies have shown that HCV antigens cluster within the liver. We investigated spatial distribution and determinants of HCV replication in human liver samples. Methods We analyzed liver samples from 4 patients with chronic HCV infection (genotype 1, Metavir scores 0-1) to estimate the proportion of infected hepatocytes and the amount of HCV viral RNA (vRNA) per cell. Single-cell laser capture microdissection was used to capture more than 1000 hepatocytes in grids, to preserve geometric relationships. HCV vRNA and interferon-induced transmembrane protein 3 (IFITM3) messenger RNA (the transcript of an interferon-stimulated gene) were measured in the same hepatocytes by quantitative polymerase chain reaction and assembled in maps to identify areas of high and low HCV replication. Results Patients' serum levels of HCV RNA ranged from 6.87 to 7.40 log10 IU/mL; the proportion of HCV-infected hepatocytes per person ranged from 21% to 45%, and the level of vRNA ranged from 1 to 50 IU/hepatocyte. Infection was not random; we identified clustering of HCV-positive hepatocytes using infected-neighbor analysis (P <.0005) and distance to the kth nearest neighbor compared with random distributions, obtained by bootstrap simulations (P <.02). Hepatocytes that expressed IFITM3 did not appear to cluster and were largely HCV negative. Conclusions We used single-cell laser capture and high-resolution analysis to show that in human liver HCV infects hepatocytes in nonrandom clusters, whereas expression of antiviral molecules is scattered among hepatocytes. These findings show that quantitative single-cell RNA measurements can be used to estimate the abundance of HCV vRNA per infected human hepatocyte and are consistent with cell-cell propagation of infection in the absence of clustered IFITM3. © 2013 by the AGA Institute.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Intrahepatic Infection; ISG; scLCM; Virology